Comorbid monosymptomatic nocturnal enuresis and snoring exhibit an additive effect on impairments in health-related quality of life. Issue 6 (December 2019) - Wolfe-Christensen, Cortney; Kovacevic, Larisa G.; Abdulhamid, Ibrahim; Lakshmanan, Yegappan
Summary: Introduction/Background: Health-related quality of life (HRQOL) is a relatively new concept in pediatrics, but it has shown to be extremely important in terms of clinical care, treatment planning, and compliance with medical and behavioral recommendations. Two groups of children who are at risk for impairments in HRQOL are those who have bed-wetting and those who snore or have sleep apnea. Objective: The present study sought to determine whether the combination of monosymptomatic nocturnal enuresis (MNE) and sleep-disordered breathing (SDB) results in diminished HRQOL in a pediatric sample. Study design: A retrospective chart review was conducted in an outpatient pediatric urology clinic and in an outpatient pulmonology clinic. Parents of the patients completed the Pediatric Sleep Questionnaire (PSQ) to assess the presence of SDB and snoring, and HRQOL was assessed using the Obstructive Sleep Apnea Syndrome–18-item (OSAS-18) scale, both validated measures, as part of the child's clinical workup. Results: One hundred fifty-two (85 males and 67 females ) patients were included and were categorized into any of the following four groups: (1) MNE only, (2) SDB only, (3) MNE + SDB, or (4) healthy control. Patients in the SDB-only group had significantly more severe SDB than those in the other groups. As such, severity of SDB was controlled for in analyses. Results revealed that the four groups significantly differed on all subscales of the OSAS-18, which are Sleep Disturbance, Physical Symptoms, Emotional Symptoms, Daytime Functioning, and Caregiver Concerns. Post hoc analyses revealed the MNE + SDB group had more impairments on each subscale. Analysis of the total impairments revealed that children with only one condition (MNE or SDB) reported similar levels of impairments in HRQOL and patients with MNE + SBD reported significantly higher levels of impairments, as it appears that these comorbid conditions have an additive effect on HRQOL. Discussion: Children with comorbid MNE and SDB are at significantly higher risk for reporting impairments in their HRQOL than children who have only one of these conditions. While it is already known that children with MNE are at risk for emotional, behavioral, and social difficulties and children with SDB are at risk for neurobehavioral difficulties, it is possible that children with both conditions are at risk for a multitude of negative consequences. Conclusion: These data emphasize the importance of urologist screening for SDB and pulmonologist screening for MNE as part of their routine clinical practice. Summary Fig. Total OSAS-18 scores by diagnostic group. HRQOL = health-related quality of life; MNE = monosymptomatic nocturnal enuresis; OSAS-18 = Obstructive Sleep Apnea Syndrome–18-item. Figure